2006
DOI: 10.1103/physreva.73.032105
|View full text |Cite
|
Sign up to set email alerts
|

Possibility for precise Weinberg-angle measurement in centrosymmetric crystals with axis

Abstract: We demonstrate that parity-nonconserving interaction due to the nuclear weak charge Q W leads to a nonlinear magnetoelectric effect in centrosymmetric paramagnetic crystals. It is shown that the effect exists only in crystals with special symmetry axis k. Kinematically, the correlation ͑correction to energy͒ has the form H PNC ϰ Q W E · ͓B ϫ k͔͑B · k͒, where B and E are external magnetic and electric fields. This gives rise to the magnetic induction M PNC ϰ Q W ͕k͑B · ͓k ϫ E͔͒ + ͓k ϫ E͔͑B · k͖͒. To be specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The well flow rate, static level and water temperature were determined. These studies showed that there are no changes in hydrodynamic, hydrochemical and temperature regime of thermal waters in undisturbed conditions over time (Mukhamedjanov et al, 1992).…”
Section: Monitoring Observations Of Usek Area Wells Can Be Divided In...mentioning
confidence: 93%
See 1 more Smart Citation
“…The well flow rate, static level and water temperature were determined. These studies showed that there are no changes in hydrodynamic, hydrochemical and temperature regime of thermal waters in undisturbed conditions over time (Mukhamedjanov et al, 1992).…”
Section: Monitoring Observations Of Usek Area Wells Can Be Divided In...mentioning
confidence: 93%
“…3T 1. The purpose of experimental works was to determine the nature of dependence of the well flow rate on water level lowering, to identify hydrogeological parameters, to identify the pattern of changes in the level, flow rate, temperature and water quality over time (Mukhamedjanov et al, 1992).…”
Section: Introductionmentioning
confidence: 99%